The The Strategic Role of Family-Friendly Policies in Enhancing Subjective Family Well-Being in Dual-Earner Families: A Quantitative Approach - Rahmi Damayanti; Euis Sunarti; Istiqlaliyah Muflikhati (Pusbindiklatren Bappenas, 2025)
The magnitude of Indonesia's family challenges has prompted many couples to rely on dual incomes to improve family well-being. One of the main challenges in advancing family-friendly policies in Indonesia is the absence of an integrated policy framework that explicitly places the family at the center of development. This study aims to analyze the influence of family-friendly policies, sources of stress, work-family balance, and family functioning on the subjective well-being of dual-income families. The data collection relied on an online survey of 200 dual-income families conducted in January–February 2025, analyzed using Pearson correlation and Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that family-friendly policies significantly enhance work-family balance, family functioning, and subjective family well-being. These findings highlight the strategic role of family-friendly policies in strengthening family life, while also contributing to the discourse on sustainable development planning by emphasizing the importance of integrating family-centered perspectives into policy frameworks.